Changes in the Social Life of Tribal People in Muara Bungo Jambi 1980-2023 - Wati, Fitri Rahma; Chaniago, Danil Mahmud; Asril, Asril (UNIVERSITAS MUHAMMADIYAH METRO, 2025)
This writing aims to analyze and reconstruct the process, causal factors, and changes that have occurred in the life of the Anak Dalam Tribe, especially those in the Bungo Jambi Regency area. The author uses a historical research method consisting of four steps, namely heuristics, source criticism, synthesis, and historiography, assisted by the use of the theory of Social Change which will be narrowed down through Auguste Comte's theory of Social Change. The results of the study can be explained that no Suku Anak Dalam is untouched by change, all Suku Anak Dalam have been touched by change, but in these changes there are those who accept only limited interests (slight changes), as well as changes in all forms (major changes). The changes that occur in the life of Suku Anak Dalam include several aspects, changes in behavior, changes in social values, changes in livelihoods, changes in thought patterns, changes in clothing styles and so on.